New models of inclusive innovation in emerging markets: the brazilian experience - Silva, Marisalvo da (My University, 2016)
Inclusive innovation is a relatively new theme on the international scene. Inclusive innovation is the means by which new goods and services are developed for and/or by the billions living on the lowest incomes. This study presents three successful approaches to reach low-income groups: Microcredit, Regional Sustainable Development Strategy, and Banking and Fluvial Correspondents. The study was conducted based on secondary data obtained from documented research and descriptive case study analyses and contributes to increase understanding of the characteristics of the inclusive innovations and strategies used to offer financial products and services.
Keywords: Inclusive innovation; Brazil; Sustainability; Financial inclusion